In the cities of the south - Seabrook, Jeremy (London, 1996)
This is an account of life in the vast and ever-expanding cities of South Asia. From Bangkok, Bombay, Dhaka, Manila, Ho Chi Minh City and Kuala Lumpur, Jeremy Seabrook brings stories of survival and uncelebrated heroism, stories with uncanny echoes of life in Britain in the early-industrial era. At the same time, he provides an analysis of the restructuring of urban life in South Asia, as the world moves towards a (3z(Bsingle integrated economy.(3y (BThe book evokes daily life, with descriptions of collective resistance, together with the extraordinary individual tales of some of the thousands of migrants who arrive daily in these megacities of the South. Jeremy Seabrook pays special attention to the position of labour, both organized and unorganized in these cities, to the unrecorded struggles of industrial workers in the suburbs in Jakarta, or garment-workers in Bangkok. In doing so, he highlights the convergences between North and South, which are likely to become sharper as workers in Britain and other Western countries are forced into even fiercer competition with those of South Asia. Jeremy Seabrook is the author of The Unprivileged, Mother and Son, The Idea of Neighbourhood, Landscapes of Poverty, Myth of the Market, A World Still to Win, The Revolt Against Change and Victims of Development.s
Keywords: Cities and towns